2016
DOI: 10.1016/j.kjms.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Rebaudioside A inhibits pentylenetetrazol‐induced convulsions in rats

Abstract: The safety of patients with epilepsy consuming sweetening agents, which is becoming increasingly prevalent for various reasons, is a topic that should be emphasized as sensitively as it is for other diseases. Patients with epilepsy consume sweetening agents for different reasons such being diabetic or overweight. They can occasionally be exposed to sweetening agents unrestrainedly through consuming convenience food, primarily beverages. This study aimed to investigate the effects of rebaudioside A (Reb-A), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Stevia R. ameliorated the high Racine's convulsion score and prolonged the latency of epileptic seizures. These findings conform to the neuroprotective actions of stevia extract and its derivatives displayed in previous studies such as scopolamine-induced memory loss [16], fructose-induced plurimetabolic changes in the hip-pocampus and amygdala [17] and the anti-convulsive effects for Rebaudioside A (derivative of stevia) on convulsions induced by a single high dose of PTZ (70 mg/kg) [18]. However, in the current study, we demonstrated the role of Stevia R. during epileptogenesis induced by repeated administration of subconvulsive doses of PTZ suggesting not only anticonvulsive but also anti-epileptic effect for Stevia extracts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Stevia R. ameliorated the high Racine's convulsion score and prolonged the latency of epileptic seizures. These findings conform to the neuroprotective actions of stevia extract and its derivatives displayed in previous studies such as scopolamine-induced memory loss [16], fructose-induced plurimetabolic changes in the hip-pocampus and amygdala [17] and the anti-convulsive effects for Rebaudioside A (derivative of stevia) on convulsions induced by a single high dose of PTZ (70 mg/kg) [18]. However, in the current study, we demonstrated the role of Stevia R. during epileptogenesis induced by repeated administration of subconvulsive doses of PTZ suggesting not only anticonvulsive but also anti-epileptic effect for Stevia extracts.…”
Section: Discussionsupporting
confidence: 91%
“…Few studies have investigated the neuroprotective effects of stevia extract and its derivatives against scopolamine-induced learning and memory deficits [16] and fructose-induced neuronal damage in the hippocampus, amygdala, and spinal cord [17]. Moreover, Rebaudioside A (derivative of stevia) significantly attenuated the PTZinduced convulsive and EEG changes [18]. Mei et al [19] concluded that Isosteviol sodium (a derivative of stevia) protects against oxidative stress and apoptosis in cardiomyocytes via activation of the Sirt-1/PGC-1α pathway.…”
Section: Introductionmentioning
confidence: 99%